Anti‐thymoglobulin induction improves neonatal porcine xenoislet engraftment and survival. (23rd December 2021) - Gao, Qimeng; Davis, Robert; Fitch, Zachary; Mulvihill, Michael; Ezekian, Brian; Schroder, Paul; Schmitz, Robin; Song, Mingqing; Leopardi, Frank; Ribeiro, Marianna; Miller, Allison; Moris, Dimitrios; et al.
Abstract: Porcine islet xenotransplantation is a viable strategy to treat diabetes. Its translation has been limited by the pre‐clinical development of a clinically available immunosuppressive regimen. We tested two clinically relevant induction agents in a non‐human primate (NHP) islet xenotransplantation model to compare depletional versus nondepletional induction immunosuppression. Neonatal porcine islets were isolated from GKO or hCD46/GKO transgenic piglets and transplanted via portal vein infusion in diabetic rhesus macaques. Induction therapy consisted of either basiliximab (n = 6) or rhesus‐specific anti‐thymocyte globulin (rhATG, n = 6), combined with a maintenance regimen using B7 costimulation blockade, tacrolimus with a delayed transition to sirolimus, and mycophenolate mofetil. Xenografts were monitored by blood glucose levels and porcine C‐peptide measurements. Of the six receiving basiliximab induction, engraftment was achieved in 4 with median graft survival of 14 days. All six receiving rhATG induction engrafted with significantly longer xenograft survival at 40.5 days ( P  = 0.03). These data suggest that depletional induction provides superior xenograft survival to nondepletional induction, in the setting of a costimulation blockade‐based maintenance regimen.